2020
DOI: 10.1093/scan/nsaa138
|View full text |Cite
|
Sign up to set email alerts
|

Humans’ pupillary contagion extends to cats and dogs

Abstract: When viewing pupil sizes change, our own pupil sizes change, a phenomenon known as pupillary contagion. This involuntary response is reliable between humans, but can be affected by familiarity and empathy. We investigated whether the pupillary contagion response occurs for humans viewing familiar species – cats and dogs – and whether it is modulated by preferences for particular species. Pupil sizes were measured while viewing cat, dog, and human images with small, medium, and large pupils. Trait empathy, cat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…This begs the question whether the effect would be seen with more natural, true to life, and ecologically valid stimuli—full-face photographs with natural irises and realistic pupils that include the corneal reflection. As with the present experiment, most of the previous studies that have found pupillary contagion have used eye-slit stimuli showing only the eyes, the bridge of the nose, and the brow, with artificial pupils (Axelsson & Fawcett, 2020; Carsten et al, 2019; Fawcett et al, 2016, 2017; Kret et al, 2014, 2015; Kret & De Dreu, 2017; Prochazkova et al, 2018; Wehebrink et al, 2018). Derksen et al (2018); however, found pupillary contagion with eye-slit stimuli only for conditions in which observers were viewing models of their own ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This begs the question whether the effect would be seen with more natural, true to life, and ecologically valid stimuli—full-face photographs with natural irises and realistic pupils that include the corneal reflection. As with the present experiment, most of the previous studies that have found pupillary contagion have used eye-slit stimuli showing only the eyes, the bridge of the nose, and the brow, with artificial pupils (Axelsson & Fawcett, 2020; Carsten et al, 2019; Fawcett et al, 2016, 2017; Kret et al, 2014, 2015; Kret & De Dreu, 2017; Prochazkova et al, 2018; Wehebrink et al, 2018). Derksen et al (2018); however, found pupillary contagion with eye-slit stimuli only for conditions in which observers were viewing models of their own ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Our first question was whether pupillary contagion would be seen in older observers as it has been in younger observers. Evidence suggests that pupillary contagion is found in diverse populations and circumstances: 4-, 6-, and 9-month-old infants who viewed eye slits (Fawcett et al, 2016, 2017), individuals with autism-spectrum disorder (Galazka et al, 2019), individuals with major depressive disorder (Wehebrink et al, 2018), and even in individuals viewing dogs and cats (Axelsson & Fawcett, 2020) though not when viewing chimpanzees (Kret et al, 2014). Given the ubiquity of pupillary contagion, we hypothesized that we would observe it in older observers.…”
mentioning
confidence: 99%
“…The pupils can change very quickly in response to minor fluctuations in luminance, cognitive processes, and arousal [ 42 , 51 , 52 ]. Some studies suggest that our eyes can sense changes in another person’s pupil sizes through mimicking the pupil size of another person or animal during social interactions [ 16 , 53 , 54 ]. However, these studies cannot reliably isolate the influence of luminance on pupil dynamics [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…These included head movements (forward, backwards or right), ears downwards or forward, pupil dilator, upper lid raiser and eyes up. Paradoxically, ears forward can signify pleasure (e.g., in mice, Mus musculus 26 ) and pupil dilation can indicate opposing states in cats (e.g., play 28 and fear 13 ) and hypervigilance in humans, 29 furthermore, dilation can also be empathic and mirror heterospecifics (e.g., humans with Canis familiaris and cats) 30 . There were no cats from the healthy‐neutral/positive category in cluster one, suggesting that this cluster of AUs, particularly those which widen and expose more of the eye 31 indicate negative emotional valence.…”
Section: Discussionmentioning
confidence: 99%